Impact of resident involvement on complication rates in revision total knee arthroplasty. Issue 6 (December 2022) - Alexander, Bradley; Watson, Jared B.; Chandler, Kelly; Sowers, Mackenzie; McGwin, Gerald; Maffulli, Nicola; Jacob, Roshan; Naranje, Sameer
الملخص: أهداف البحث: نتيجة لازدياد عدد عمليات تقويم مفصل الركبة، فإن عدد عمليات مراجعة تقويم مفصل الركبة مستمر في الارتفاع. لكن عدد جراحي العظام المدربين على تقويم المفاصل لم يواكب هذه الازدياد، وسيقع العبء المتزايد في النهاية على عاتق جراحي العظام غير المتخصصين. أظهرت الأبحاث أن مشاركة الأطباء المقيمين في عمليات تقويم مفصل الركبة الأولية لا ترتبط بزيادة مضاعفات ما بعد الجراحة، ولكن عمليات مراجعة تقويم مفصل الركبة أكثر تعقيدا ولم يتم دراسة تأثير مشاركة المقيمين بشكل جيد. طرق البحث: باستخدام قاعدة بيانات البرنامج الوطني لتحسين جودة الجراحة بالكلية الأمريكية للجراحين، شملت هذه الدراسة 1834 عملية مراجعة تقويم مفصل الركبة أجريت بين عامي 2008 و 2012. من هذه العمليات، شارك الأطباء المقيمون في 863 عملية. تم تصنيف وتحليل المعلومات الديموغرافية، والأمراض المصاحبة، وأوقات الجراحة، ومدة الإقامة، ومضاعفات ما بعد الجراحة لمدة 30 يوما، حسب مشاركة الأطباء المقيمين. النتائج: لم ترتبط مشاركة الأطباء المقيمين مع زيادة مهمة في المضاعفات على المدى القصير. كانت أوقات العمليات أطول بشكل ملحوظ مع مشاركة المقيمين (147.5 دقيقة مع مشاركة المقيمين مقابل 124.55 دقيقة بدون مقيم). كما كانت مدة الإقامة بعد الإجراءات بمشاركة المقيمين أعلى بمقدار 0.34 يوما، لكن هذا لم يصل إلى الأهمية الإحصائية. الاستنتاجات: ارتبطت مشاركة المقيمين في مراجعة تقويم مفصل الركبة بزيادة كبيرة في وقت الجراحة. ومع ذلك، لم تكن هناك زيادة كبيرة في معدل المضاعفات بعد الجراحة في غضون 30 يوما. تدعم هذه النتائج استمرار مشاركة المقيمين في مراجعة حالات تقويم مفصل الركبة وإدارة ما بعد الجراحة. Abstract: Objectives: The number of revision total knee arthroplasty (TKA) procedures continues to rise, a direct consequence of the increase in primary TKA. The number of arthroplasty-trained orthopaedic surgeons has failed to increase at a corresponding rate, and the increased burden will ultimately fall on non-specialized orthopaedists. Resident involvement in primary TKA has not been found to increase postoperative complications, but revision TKA is more complex and the impact of resident involvement has not been well studied. Methods: Using the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) database, this study identified 1834 revision TKA procedures between the years 2008 and 2012. Of these procedures, 863 included resident involvement. Demographic information, comorbidities, operative times, length of stay (LOS), and 30-day postoperative complications were stratified by resident and non-resident involvement and analyzed. Results: Resident involvement was not associated with a significant increase in short-term complications. Operative times were significantly longer with resident involvement (147.50 min with resident involvement vs. 124.55 min without a resident, p < 0.001). Length of stay after procedures with resident involvement was higher by 0.34 days, but this did not reach significance (p = 0.061). Conclusion: Resident involvement in revision total knee arthroplasty was associated with a significant increase in operative time; however, there were no significant increases in postoperative complication rates within 30 days. These findings support continued resident involvement in revision total knee arthroplasty cases and postoperative management.